DEVELOPMENT OF CANVA-BASED MEDIA FOR JAMBI CULTURE AND LOCAL WISDOM TO BIPA STUDENTS - Rahmawati, Sophia; Bambang, Siti Enik Mukhoiyaroh; Wardani, Diah Octavia Kusuma; Putri, Ratumas Aisyah; Suhesti, Herni (Jurnal Ilmiah Bina Bahasa, 2025)
The integration of local wisdom into digital learning media for Indonesian for Foreign Speakers (BIPA) remains limited, particularly in beginner-level instruction. Foreign learners require visual and interactive media to understand cultural values, social practices, and regional traditions in a contextual manner. This study aims to develop Canva-based digital learning media that integrates Jambi local wisdom to support cultural learning in BIPA classes. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. Seventeen BIPA students at the University of Jambi participated in the product trial. A pretest–posttest design was applied to assess learning improvement, and data were analyzed using the Wilcoxon signed-rank test due to the small sample size and non-normal data distribution. The results indicate a statistically significant improvement in students’ learning outcomes (p = 0.001) with a large effect size (r = 0.833). Although the limited number of participants limits generalization, the findings demonstrate that Canva-based digital media effectively enhance cultural understanding and learning engagement in BIPA instruction. This study contributes to BIPA pedagogy by offering a practical model for integrating local wisdom into digital language learning media.